Outsides and outsiders: Environmental critique in Leonard Woolf's The Village in the Jungle and Romesh Gunesekera's Reef. (March 2015) - Lavery, Charne
In Leonard Woolf's The Village in the Jungle, the jungle is depicted as a great sea. It represents a potent outside, an unknowable, unconquerable boundary zone characterized by natural and supernatural evils. Romesh Gunesekara's Reef depicts the island-surrounding Indian Ocean in similar terms — the undersea world is described as an ungovernable jungle, and the ocean an ever-encroaching danger. Both novels highlight the metaphoric importance of the natural world in their titles: it is the oceanic reef and the encircling jungle that form the spatial and discursive limits to the imagined island. In different ways, these Sri Lankan narratives engage with ways of imagining the jungle and ocean as outside space, interrogating their construction as boundless externality. In addition, they are marked by a sympathetic portrayal of indigenous and disenfranchised perspectives, through the villager protagonists and the servant-boy narrator, suggesting an analogous critique of the transference of ideas of externality onto human populations. This article investigates a way in which these novels intersect at the point of engagement between ecocritical and postcolonial studies, through their imaginative mapping of outsides and outsiders.